Exosome Released FZD10 Increases Ki-67 Expression via Phospho-ERK1/2 in Colorectal and Gastric Cancer - Scavo, Maria Principia; Rizzi, Federica; Depalo, Nicoletta; Armentano, Raffaele; Coletta, Sergio; Serino, Grazia; Fanizza, Elisabetta; Pesole, Pasqua Letizia; Cervellera, Alessandra; Carella, Nicola; Curri, Maria Lucia; Giannelli, Gianluigi (Frontiers in Oncology, 2021)
Frizzled (FZD) proteins are primary receptors for Wnt signaling that activates the mitogen-activated protein kinase (MAPK) pathways. Dysfunction of Wnt signals with consequently abnormal activation of MAPK3 pathways was found in colorectal cancer (CRC) and gastric cancer (GC). Upregulation of FZD10 protein, localized in the exosomes isolated from plasma of CRC and GC patients, was associated with a poor prognosis. Herein, the expression levels of circulating FZD10 were found to be strongly correlated to their expression levels in the corresponding tissues in CRC and GC patients. Bioinformatic prediction revealed a link between FZD10 and Ki-67 through MAPK3. In both CRC and GC tissues, pERK1/2 levels were significantly increased at more advanced disease stages, and pERK1/2 and Ki-67 were correlated. Silencing of FZD10 in CRC and GC cells resulted in a significant reduction of pERK1/2 and Ki-67 expression, while subsequent treatment with exogenous exosomes partially restored their expression levels. The strong correlation between the expression of Ki-67 in tissues and of FZD10 in exosomes suggests that the exosome-delivered FZD10 may be a promising novel prognostic and diagnostic biomarker for CRC and GC.